Sex- and age-related differences of HRQOL change in cardiac rehabilitation. (3rd October 2022) - Jellestad, L; Auschra, B; Von Kanel, R; Euler, S; Hermann, M
Abstract: Introduction: Health-related quality of life (HRQOL) has emerged as a valid and disease-specific outcome measure in cardiac patients. Cardiac rehabilitation (CR), a core component of secondary prevention, not only improves cardiovascular outcomes, but also HRQOL. Unfortunately, CR is still underutilized, especially among women and older patients. Aim of this study was to highlight age- and sex-specific effects of CR on HRQOL. Method: A sample of 8286 patients (mean age 69.2±11.47 years; men 67.8±11.29, women 72.2±11.25) was analyzed. Patients were prospectively asessed from 2012 to 2018 in six Swiss CR clinics. HRQOL was measured at CR entry and discharge using the MacNew Heart Disease questionnaire. In multivariate analyses, we estimated sex- and age-specific changes in HRQOL during CR, adjusting for clinical characteristics. Results: Women scored lower in any subdomain of HRQOL on admission to CR (social M = 5.05 (SD = 1.3); emotional M = 5.06±1.17; physical M = 4.36±1.72), compared to men (social M = 5.2±1.23); emotional M = 5.35±1.1; physical M = 4.43±1.76). Women showed greater improvement of social (F=10.98, p<0.001), emotional (F=17.73, p<0.001) and physical HRQOL (F=9.47, p=0.002). In a subgroup of elderly patients (>76 years) female sex predicted higher changes in emotional (F=10.878, p<0.001), but not in social (F=1.424, p=0.232) and physical HRQOL (F=2.272, p=0.132). Conclusion: Women report poorer HRQOL in all subdomains at CR entry compared to men, but in turn particularly benefit from CR in this regard. In older patients, this is particularly true for emotional HRQOL. Our results indicate that sex- and age-specific needs of cardiac patients should be considered during CR. Funding Acknowledgement: Type of funding sources: None.